2013
DOI: 10.1016/j.jbior.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C-β in immune cells

Abstract: Great progress has recently been made in structural and functional research of phospholipase C (PLC)-β. We now understand how PLC-β isoforms (β1-β4) are activated by GTP-bound Gαq downstream of G protein-coupled receptors. Numerous studies indicate that PLC-βs participate in the differentiation and activation of immune cells that control both the innate and adaptive immune systems. The PLC-β3 isoform also interplays with tyrosine kinase-based signaling pathways, to inhibit Stat5 activation by recruiting the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 69 publications
(68 reference statements)
1
37
0
Order By: Relevance
“…PI-PLC ␤ isozymes also participate in the differentiation and activation of immune cells that control both the innate and adaptive immune systems ( 72 ). In particular, loss of both PI-PLC ␤ 2 and PI-PLC ␤ 3 isozymes is associated with an impaired T-cell migration that is caused by an inability to increase the intracellular calcium.…”
Section: Pi-plc In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…PI-PLC ␤ isozymes also participate in the differentiation and activation of immune cells that control both the innate and adaptive immune systems ( 72 ). In particular, loss of both PI-PLC ␤ 2 and PI-PLC ␤ 3 isozymes is associated with an impaired T-cell migration that is caused by an inability to increase the intracellular calcium.…”
Section: Pi-plc In Diseasementioning
confidence: 99%
“…In particular, loss of both PI-PLC ␤ 2 and PI-PLC ␤ 3 isozymes is associated with an impaired T-cell migration that is caused by an inability to increase the intracellular calcium. Interestingly, human T-cells from elderly people show a reduced expression of PI-PLC ␤ 2, suggesting that a specifi c impairment of this enzyme in aged T lymphocytes might contribute to the immune suppression mechanisms in this group of people ( 72,73 ). Moreover, PI-PLC ␤ 2 downregulation plays an important role in M1-M2 macrophage differentiation, whereas PI-PLC ␤ 3 activity is essential for promoting macrophage survival, especially in atherosclerotic plaques, so that PI-PLC ␤ 3 could be a potential specifi c molecular target for the treatment of atherosclerosis ( 74 ).…”
Section: Pi-plc In Diseasementioning
confidence: 99%
“…Previous studies demonstrated that PLC is activated through a combination of the activated GPCR and Gaq, integrin and extracellular matrix, and growth factor and its receptor in PLC signaling pathways (Kawakami and Xiao, 2013). In this study, the expression of PLCD4 (encoding a member of the PLCd family) was up-regulated in rat HCs.…”
Section: Discussionmentioning
confidence: 53%
“…PLC, a very important phosphoinositidespecific and key enzyme in cellular signaling, is categorized into 6 classes, including the b (1-4), g (1, 2), d (1, 3, 4), e, x, and h (1, 2) types (Fukami et al, 2010). The PLC pathway can be activated by different receptors (Kawakami and Xiao, 2013), and is thus classified into 3 branches, including G protein-coupled receptor (GPCR)/PLC, growth factor receptor (GFR)/PLC, and integrin/PLC. Among these, the GPCR/PLC branch activates PLC through GPCR→G proteins (Ga, Gb, Gg)→AC→cAMP→EPAC→Rap or RhoGEF→Rho/Rac.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the PLC-β subfamily appears to be essential for the generation of IP 3 , DAG, and mobilization of Ca 2+ (Bach et al 2007). Moreover, PLC-β plays a critical role in activation of chemoattractant-induced integrin, cellsubstrate adhesion, and in the movement and antibody production of B lymphocytes (Kawakami and Xiao 2013). Thus, PLC-βs are involved in the specialization and activation of Fig.…”
Section: Discussionmentioning
confidence: 99%